2013
DOI: 10.7314/apjcp.2013.14.8.4811
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Blood Group and Social Factors in Carcinoma Cervix in a Semi-Urban Population in India

Abstract: Background: To assess the significance of social factors as risk factors for carcinoma cervix and to determine the significance of blood group to prevalence of carcinoma cervix in a semi-urban population of Kolar, Karnataka, India. Materials and Methods: One hundred cases of carcinoma cervix were included in the study, along with 200 females of the same ages considered as controls. Case details were collected from the hospital record section regarding social factors and blood groups and the data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, our investigation showed there is no significant between ABO and Rh blood groups and cervix cancer. However, some studies suggested that the B blood group may as a risk factor for cervix carcinoma 2 , 3 . Although another study reported O blood group was slightly associated with Cervical Carcinoma 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our investigation showed there is no significant between ABO and Rh blood groups and cervix cancer. However, some studies suggested that the B blood group may as a risk factor for cervix carcinoma 2 , 3 . Although another study reported O blood group was slightly associated with Cervical Carcinoma 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Cervix cancer is second the most common cancer in females that mainly occurs in developing countries 2 . Studies show that control and prevention are crucial for this deadly cancer 3 . Among different demographical and biological factors, patient blood type could play an essential role as a predisposing factor in many diseases.…”
Section: Introductionmentioning
confidence: 99%